Autoantibodies Against Carbonic Anhydrase I and II in Patients with Acute Myeloid Leukemia - Ahmet Menteşe; Nergiz Erkut; Selim Demir; Serap Özer Yaman; Aysegül Sümer; Seniz Doğramacı; Ahmet Alver; Mehmet Sönmez (Turkish Journal of Hematology, 2017)
Objective: Cancer, one of the principal causes of death, is a global social health problem. Autoantibodies developed against the organism's self-antigens are detected in the sera of subjects with cancer. In recent years carbonic anhydrase (CA) I and II autoantibodies have been shown in some autoimmune diseases and carcinomas, but the mechanisms underlying this immune response have not yet been explained. The aim of this study was to evaluate CA I and II autoantibodies in patients with acute myeloid leukemia (AML) and to provide a novel perspective regarding the autoimmune basis of the disease. Materials and Methods: Anti-CA I and II antibody levels were investigated using ELISA in serum samples from 30 patients with AML and 30 healthy peers. Results: Anti-CA I and II antibody titers in the AML group were significantly higher compared with the control group (p=0.0001 and 0.018, respectively). A strong positive correlation was also determined between titers of anti-CA I and II antibodies (r=0.613, p=0.0001). Conclusion: Our results suggest that these autoantibodies may be involved in the pathogenesis of AML. More extensive studies are now needed to reveal the entire mechanism.